Carcass quality of autochthonous Cika cattle - Simčič, Mojca (Acta agriculturae Slovenica, 2008)
The Cika cattle is the only Slovenian autochthonous cattle breed, counting around 1,600 animals in 2007. The breeding goal for Cika cattle is dual purpose with the emphasis on milk production. However, Cika cattle is mostly reared in the cow-calf system. To a smaller extent Cika cattle is still used for milk production in the traditional regions for Alpine dairy-farming. Our main interest was to get an insight into carcass quality of Cika cattle. The data used in this survey were collected in slaughterhouses in the years 2005 through 2007. Out of all slaughtered cattle in 2007 the share of slaughtered Cika cattle was 0.24%. According to the category, the slaughtered animlas were very heterogenic in carcass weight which is seen in rather large standard deviations. The average carcass weight of A category (bulls under 24 months of age) was 260.3 kg. The majority of bulls under 24 months of age and calves were classified in conformation class O (57.1 and 47.8%), whereas bulls over 24 months of age were mostly classified in the conformation class R. The majority of calves (88.1%), bulls under 24 months of age (55.8%) and bulls over 24 months of age (49.5%) were classified in fatness class 2. Most of Cika cattle are reared extensively on small farms, mostly on mountain pastures without any additional concentrates. This could present the basis and the opportunity for Cika breeders to promote beef from Cika cattle on the market and to increase their income. Autochthonous Cika is well adapted to the environment and helps to maintain biodiversity and sustainable agricultural production, especially in less favourable agricultural areas.
Keywords: govedo; pasme; klavna kakovost; Slovenia; Slovenija